Cryptococcus neoformans serotype A glucuronoxylomannan-protein conjugate vaccines: synthesis, characterization, and immunogenicity. - Devi, S J (1991)
We synthesized Cryptococcus neoformans serotype A glucuronoxylomannan (GXM) conjugate vaccines under conditions suitable for human use to prevent disseminated cryptococcosis. The purified, sonicated GXM was derivatized with adipic acid dihydrazide through either hydroxyl or carboxyl groups and then covalently bound to tetanus toxoid (TT) or Pseudomonas aeruginosa exoprotein A (rEPA). The immunogenicity of these conjugates was evaluated in BALB/c and general purpose mice by subcutaneous injection in saline. The conjugates elicited higher GXM antibody responses than GXM alone. Booster immunoglobulin G (IgG) and IgM responses were elicited by all conjugates in BALB/c mice. The conjugates prepared through hydroxyl activation (GXM-TT2 and GXM-rEPA) were more immunogenic than the one prepared through carboxyl activation (GXM-TT1). GXM antibody response was enhanced by the administration of monophosphoryl lipid A 2 days following the injection of GXM-TT2 (P less than 0.03). The conjugates also elicited IgG antibodies to the carrier proteins. Gel diffusion tests using conjugate-induced hyperimmune sera and chemically modified GXMs suggested that the specificity of GXM-TT1-induced antibodies was conferred by the O-acetyl groups. Hyperimmune sera generated by GXM-TT2 precipitated with the chemically unmodified and the de-O-acetylated GXMs but not with the carboxyl-reduced and de-O-acetylated GXM. GXM-TT2-induced hyperimmune serum also precipitated with the capsular polysaccharides of C. neoformans serotypes D, B, and C. The conjugate vaccines prepared through hydroxyl activation of the GXM are sufficiently immunogenic and appear to be suitable for clinical evaluation.